CLOSED FRIEDMANN MODEL IN A MODIFIED GRAVITATIONAL THEORY - Sharshekeev, O.Sh.; Sagynbaev, M.; Taukenova, A.S. (Recent Contributions to Physics, 2011)
We consider a closed Friedmann model in modified theory of gravity (including the Riemann tensor). The dependence of the scale factor on time for a hot ultrarelativistic case (p=ε/3). In this case the exponent of the Riemann tensor chosen as α = 1/2. If we set the parameter A = sqrt(6) , then, we obtain a solution in which there is no physical singularity. A similar solution was obtained at A = sqrt(3).